Clinical Significance of Improved Intraoperative Neurophysiological Monitoring Signal during Spine Surgery: A Retrospective Study of a Single-Institution Prospective Cohort - Seung Myung Wi; Hui-Jong Lee; Taehoon Kang; Sam Yeol Chang; Sung-Min Kim; Bong-Soon Chang; Choon-Ki Lee; Hyoungmin Kim (Asian Spine Journal, 2020)
Study Design Retrospective case series. Purpose We reviewed the cases that showed significant improvement of intraoperative neurophysiological monitoring (IONM) signals during spine surgery to assess whether there is a correlation with signal improvement and postoperative clinical status and its clinical significance. Overview of Literature To reduce the risk of neural injury, many spine surgeons are using multimodality IONM. Although many studies attempted to identify valid alarm criteria for predicting postoperative neurologic deterioration, studies concerning the improvement of IONM signals are rare. Methods We reviewed all spine surgery cases with IONM data treated at our department between January 2013 and May 2017. We found cases showing significant IONM signal improvements. We prospectively analyzed the neurological and clinical outcomes of these patients and compared outcomes pre- and postoperatively. Results Among 317 cases with the IONM data, we found 29 cases that showed IONM signal improvement compared with baseline. There were 27 cases of compressive myelopathy: 22 had a degenerative cause at the cervical spine, and five, at the thoracic spine. There were two cases of huge neurogenic tumor each at the craniovertebral junction and at the lumbar spine. Both motor-evoked potentials (MEPs) and somatosensory-evoked potentials (SSEPs) signals were improved in six cases, only the MEPs signal improved in 10, and only SSEP signal improved in 13 cases. All cases showed the IONM signal improvement consistently after the decompression procedure during surgery. All patients had a significant improvement in neurological function and subjective symptoms, and none had neurologic deterioration postoperatively. Conclusions Improvement of IONM signals during surgery may indicate that no unrecognized neural injury occurred during surgery and a favorable postoperative neurological outcome can be expected.